(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
This study has investigated the physical characteristics and needs of pregnant women to introduce a scientific and practical design of bellyband to satisfy pregnant women demand. Structure and material of supporting bellyband have been introduced in the study and its functional rationality also has been verified by many testers. Finally, the experiment result has been proved that the design of supporting bellyband has helped pregnant women to ease the burden of their waist efficiently and effectively after analysed the result very carefully.